Measurement of the top pair production cross section in 8 TeV proton-proton collisions using kinematic information in the lepton+jets final state with ATLAS - Aad, G. (2015)
A measurement is presented of the tt¯ inclusive production cross section in pp collisions at a center-of-mass energy of s=8  TeV using data collected by the ATLAS detector at the CERN Large Hadron Collider. The measurement was performed in the lepton+jets final state using a data set corresponding to an integrated luminosity of 20.3  fb−1. The cross section was obtained using a likelihood discriminant fit and b-jet identification was used to improve the signal-to-background ratio. The inclusive tt¯ production cross section was measured to be 260±1(stat)−23+22(stat)±8(lumi)±4(beam)  pb assuming a top-quark mass of 172.5 GeV, in good agreement with the theoretical prediction of 253−15+13  pb. The tt¯→(e,μ)+jets production cross section in the fiducial region determined by the detector acceptance is also reported.